ANALISIS PERAN ORANG TUA DALAM MEMBENTUK KARAKTER TANGGUNG JAWAB ANAK MELALUI PEMBIASAAN KEGIATAN SEHARI-HARI DI DESA SUNGELEBAK - Aini Putri, Ella Nur; Nikmah, Khoirotun; Suradji, Muchamad (Jurnal Murid, 2024)
Parents are role models for their children. The character of children's responsibility can be accustomed from an early age with parental guidance and direction. Children can understand good attitudes and behaviors taught by parents and can be accustomed through learning and practicing them in daily activities. The objectives of this study are (1) to understand how the role of parents in the formation of children's responsible character (2) to explain what factors can affect children's character. This type of research is a qualitative descriptive research that describes the object or subject matter that is studied absolutely without being influenced by personal opinions or views. From the results of this study, the role of parents in shaping the character of children's responsibility runs well in accordance with its implementation in daily activities.